Experience of a telehealth and education program with maternal and perinatal outcomes in a low-resource region in Colombia - María Fernanda Escobar; María Paula Echavarria; Hilda Vasquez; Daniela Nasner; Isabella Ramos; María Antonia Hincapié; Stephanie Pabon; Juan Pedro Kusanovic; Diana Marcela Martínez-Ruíz; Javier Andrés Carvajal (BMC, 2022)
Abstract Introduction Maternal morbidity and mortality rates associated with perinatal care remain a significant public health concern. Rural populations from low and middle-income countries have multiple barriers to access that contribute to a lack of adherence to prenatal care, and high rates of maternal mortality and morbidity. An intervention model based on telehealth and education was implemented between a tertiary high complex care hospital and a second-level hospital from a limited source region. Objectives We sought to identify an association in maternal and perinatal care quality indicators after implementing a model based on telehealth and education for patients with obstetric emergencies between two hospitals in a southwestern region of Colombia. Methods We conducted an ecological study between 2017 and 2019 to compare before and after obstetric emergency care through telemedicine from a secondary care center (Hospital Francisco de Paula Santander-HFPS) to the referral center (Fundación Valle del Lili-FVL). The intervention included verification visits to determine the installed capacity of care, a concerted improvement plan, and on-site educational training modules in obstetric and perinatal care. Results There were 102 and 148 patients treated before and after telemedicine implementation respectively. Clinical indicators after model implementation showed a reduction in perinatal mortality of 29%. In addition, a reduction in the need for transfusion of blood products due to postpartum hemorrhage was observed as well as the rate of eclampsia. Conclusions Implementing a model based on telehealth and education between secondary and tertiary care centers allowed the strengthening of the security of care in obstetric emergencies and had a positive effect on perinatal mortality.